1980
DOI: 10.1111/j.1432-1033.1980.tb04582.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Mobility Inside Pyruvate Dehydrogenase Complexes as Reflected by Laser‐Pulse Fluorometry

Abstract: The fluorescence decay curves of the flavin in all pyruvate dehydrogenase complexes studied here are consistent with a two-exponential fit. One of the lifetimes calculated is very short, as demonstrated by experiments in which a mode-locked argon-ion laser was used for excitation. In three complexes out of the four which were investigated, about equal weights for the amplitudes of the two lifetimes are found. In the three-component complex from Azotohacter vinelundii this is not the case. No effects of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In lipoamide dehydrogenase, however, the fluorescence quantum yield is relatively high. Also the average fluorescence lifetime is quite long [6]. Our timeresolved fluorescence and fluorescence anisotropy results provide clear evidence, that the flavin microenvironments in both enzymes are different.…”
Section: Introductionmentioning
confidence: 54%
“…In lipoamide dehydrogenase, however, the fluorescence quantum yield is relatively high. Also the average fluorescence lifetime is quite long [6]. Our timeresolved fluorescence and fluorescence anisotropy results provide clear evidence, that the flavin microenvironments in both enzymes are different.…”
Section: Introductionmentioning
confidence: 54%
“…The position of this sequence in the E2o chain corresponds with that of the much shorter (alanine + proline)-rich sequence (residues 370-377) of the E2p chain referred to above, although the sequences of the E2p and E2o chains are not otherwise markedly homologous in this region (Spencer et al, 1984). If this region of the E2p and E2o polypeptide chains, which links the E3-binding domain to the inner core-forming catalytic domain, does enjoy some degree of conformational freedom in the intact complexes, it might provide a structural basis for interpreting the hitherto puzzling fluorescence data which suggest that E3 bound to the PDH complex is quite mobile (Grande et at., 1980). Further genetic reconstructions of the E2p and E2o polypeptide chains should enable unequivocal answers to these questions to be obtained.…”
Section: Discussionmentioning
confidence: 93%
“…elsdenii is tightly associated with the apoprotein. This is an interesting observation with regard to nanosecond fluorescence data on the pyruvate dehydrogenase complex [42] for which it was found that the protein-bound flavin possesses a certain internal freedom on the nanosecond timescale. It is possible that these observations are linked to the specific biological functions of the proteins under consideration.…”
Section: Protein-bound F M Nmentioning
confidence: 86%